Implementasi Metode Dirosati untuk Meningkatkan Kemampuan Membaca al-Qur’an Bagi Anak Usia Dini - Ning Mukaromah; Nur Anisah (Lajnah Ta'lif wan Nasyr Nahdlatul Ulama (LTN-NU) Kabupaten Probolinggo, 2022)
Reading the Qur'an is a beneficial practice for Muslims because it allows them to understand, appreciate, and apply the contents of the Qur'an in their daily lives. Learning the Qur'an should be introduced to students at a young age because there is a large learning potential in childhood. The objectives of this study are as follows: 1) describe the implementation of the Dirosati method? 2) Is there an evaluation form? 3) What are your strengths and weaknesses? The descriptive research method was used in this study, which took a qualitative approach. The data for this study came from ustadz and ustadzah TPQ PP Anak al-Qodiri Jember. Instruments for data collection include interviews, observation, and documentation. In terms of research findings, 1) Individual or private implementation of the Dirosati method. b) Individualistic-classical. c) See classical read. d) The media. 2) The type of evaluation used is a) formative evaluation. b) Formative assessment. c) Diagnostic testing. 3) Advantages: a) CBSA is used in this Dirosati method. b) The planning is more practical. c) Keep a book of recitation summaries, memorization guidelines, and prayer guides for yourself. and d) Coaching is done once a month. Weaknesses include: a) a lack of learning media. b) The Dirosati method is seldom used. c) It takes a long time, and d) The Creator has invented a new method, namely 'Allimna.